Annual Accounting Information and Stock Price Reactions: Evidence from Nigeria Deposit Money Banks in West Africa - OLAOYE, Clement Olatunji; EKUNDAYO, Temitope Ayodele; EKUNDAYO, Temitope Ayodele (Annals of Spiru Haret University. Economic Series, 2022)
This paper examined the value relevance of accounting information and stock prices in Deposit Money Banks in Nigeria. Specifically, it assessed the behaviour of share prices in relation to accounting information in terms of earnings per share, book value per share, dividends per share and return on assets. The study adopted the expo-facto research design and the study elements covered all the 18 listed Deposit Money Banks; out of which, 10 Banks were selected as the study participants and this was achieved through a random sampling technique. The study covered 10 years, spanning from 2010-2019 and data were sourced from the fact book of the Nigeria Stock Exchange (NSE) and audited annual financial reports of the sampled banks. The estimation technique adopted in this study was panel data analysis technique. This was carried out after descriptive statistics and Pearson correlation. It was discovered that earnings per share, book value per share and dividends per share exert a positive and significant effect on stock prices and that return on assets exerts a positive and insignificant effect on stock prices. Based on the findings, it was established that accounting information has a positive effect on stock prices. Thus, it was recommended that timely and adequate accounting information should be made available by the management of Deposit Money Banks in Nigeria to induce the interest of investors and that investors are urged to pay more attention to earnings per share, book value per share and dividend per share in their investment decisions